Experimental investigation of correction factor for VIV amplitude of flexible bridges from an aeroelastic model and its 1:1 section model. (15th June 2017) - Zhou, S.; Hua, X.G.; Chen, Z.Q.; Chen, W.
Highlights: A novel aeroelastic model for studying vortex-induced vibrations is developed. Both the novel aeroelastic model and its section model of the same size are tested in wind tunnel in smooth flow. The maximum VIV amplitude measured from both models are compared to define the correction factors between them. The experimental correction factors are compared with those calculated from theoretical models. Abstract: Evaluation of the maximum amplitudes of vortex-induced vibrations (VIV) in suspension bridges is mainly relied upon section model wind tunnel tests of bridge decks. Extrapolation to prototype responses requires addition correction to take into account the differences both in structural mode shape and in spanwise correlation of excitation forces between the section model and the prototype. The paper presents the results of VIV amplitudes measured on an aeroelastic model and on its section model with the same size of cross-section. The aeroelastic model is a new, elastically multi-supported one which is capable of reproducing the closely-spaced vertical modes of a suspension bridge. The vortex-induced vibrations for a number of vertical modes were successfully measured from the aeroelastic model test in smooth flow. The spring-mounted section model having the same size of cross-section as the aeroelastic model was also tested in smooth flow at the same mass, damping ratio and vibration frequency. It is shown that both the VIV onset wind velocity and lock-in range for each mode of vibration are in good agreement between the aeroelastic model and the section model. The aeroelastic model consistently produces a roughly 30% higher maximum amplitude than the section model for the observed modes of vibration. It is confirmed that the combined three-dimensional (3D) effects due to mode shape and imperfect correlation of excitation forces amplify the VIV amplitudes and disregarding these effects may underestimate the VIV amplitudes for section model tests. A correction factor of 1.3 for the VIV amplitude of vertical modes in suspension bridges may be adopted for practical use when extrapolating the section-model results to their corresponding full-scale values.